2011
DOI: 10.1016/j.molbiopara.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of three protozoan homologs of tryptophanyl-tRNA synthetase

Abstract: Tryptophanyl-tRNA synthetase (TrpRS) is an essential enzyme that is recognizably conserved across all forms of life. It is responsible for activating and attaching tryptophan to a cognate tRNATrp molecule for use in protein synthesis. In some eukaryotes this original core function has been supplemented or modified through the addition of extra domains or the expression of variant TrpRS isoforms. The three TrpRS structures from pathogenic protozoa described here represent three illustrations of this malleabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…Crystal structures of AlaX-S (specific to Ser-tRNA Ala ) and AlaX-M (specific to Ser-tRNA Ala and Gly-tRNA Ala ) from archaeon Pyrococcus horikoshii have been reported [20], [21]. Our earlier computational investigations had revealed that P. falciparum contains a variant WRS where the catalytic domain is fused to a distant homolog of the free-standing, proofreading factor AlaX [22], [23]. Cryptosporidium parvum genome also contains a single WRS gene that possesses an N-terminal AlaX like domain in addition to the conserved catalytic WRS domains [23].…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures of AlaX-S (specific to Ser-tRNA Ala ) and AlaX-M (specific to Ser-tRNA Ala and Gly-tRNA Ala ) from archaeon Pyrococcus horikoshii have been reported [20], [21]. Our earlier computational investigations had revealed that P. falciparum contains a variant WRS where the catalytic domain is fused to a distant homolog of the free-standing, proofreading factor AlaX [22], [23]. Cryptosporidium parvum genome also contains a single WRS gene that possesses an N-terminal AlaX like domain in addition to the conserved catalytic WRS domains [23].…”
Section: Introductionmentioning
confidence: 99%
“…1A). While not tested for Pf -cTrpRS, the deletion of the first part of N-terminal extension did not affect the aminoacylation activity of the homologous apicomplexan Cryptosporidium parvum TrpRS [25]. The construct was cloned into the AVA0421 vector for expression in E. coli [27].…”
Section: Methodsmentioning
confidence: 99%
“…As part of our ongoing efforts to explore aaRSs as anti-parasitic drug targets [14, 1925], we have determined the crystal structure of one of the two tryptophanyl-tRNA synthetases from P. falciparum . Like many other higher eukaryotes, P. falciparum has two genes encoding for TrpRS.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the T. brucei cytosolic TrpRS has been partially obtained, sharing a 56 % identity with the human enzyme (Merritt et al 2011 ). Although the portion of the enzyme expected to interact with the tRNA anticodon arm was not solved, a good superposition with the helical regions that contain residues involved in binding the anticodon in the human (Lys 431, Ser 378, and Thr 427) and yeast TrpRS-tRNA…”
Section: Tryptophanyl-trna Synthetasementioning
confidence: 99%
“…The overall error rate in translation is approximately 10 −4 , indicating that protein synthesis is accomplished through a high-fi delity process, necessary for the cell's life maintenance (Loftfi eld and Vanderjagt 1972 ;Ibba and Soll 1999 ;Crain et al 2002 ;Charrière et al 2006 ;Bruske et al 2009 ). Although previously believed that in all organisms there were 20 aaRSs (one for each amino acid known at the time) and only one route for tRNA aminoacylation, we now know it is not the case, and indirect pathways of aa-tRNA formation as well as new amino acids have been described (Hao et al 2002 ;Sheppard et al 2008 ;Merritt et al 2011 ). Nevertheless, in the eukaryotic nucleus there are at least 20 of these enzymes (encoded by one or more genes) and the tRNAs are charged through a direct route, with the exception of the selenocysteinyl-tRNA Sec .…”
Section: Introductionmentioning
confidence: 99%